Mali - Private Sector Assistance Grant - Mastri, Lawrence (World Bank, Washington, DC, 2012)
The principal objective of the project was to help foster the development of private sector enterprises, so that they could lead the growth of Mali's economy. The project aimed at putting in place mechanisms and measures to support the government's strategy of breaking from past reliance on the public sector. The project proposed to achieve this by: (a) completing implementation of improvements to the regulatory environment that had been introduced starting in the late eighties; (b) assisting a private business support structure, APEP, the Agence pour la Promotion de l'Entreprise Privee, to coordinate a program of institutional support to private non-financial enterprises; (c) improving the functioning of economic chambers (principally the Chamber of Commerce and Industry of Mali), the Government's office charged with public enterprise reform, BEP, and departments of the administration responsible of administering regulations affecting private enterprises; and (d) inducing the strengthening of the banking sector and the preparation of a coherent financial sector strategy.